THE ROLE OF LITERATURE IN ESP CLASSROOM (Proceedings of International Educators Conference, 2023)
In this thesis we will walk around mainly on profits and negative sides of using literature in language teaching, with special emphasis on its potential use in English for specific purposes (ESP) classroom. Predominantly, we will give an appraisal of some information regarding the use of literature in English as a foreign language. In addition, we will point out the importance of literature in ESP classrooms.